CD10 (Neutral Endopeptidase) expression in myoepithelial cells of salivary neoplasms - Neves, Catarina de Oliveira; Soares, Andresa Borges; Costa, Ana Flávia; Araújo, Vera Cavalcanti de; Furuse, Cristiane [UNESP]; Juliano, Priscila Bianchi; Altemani, Albina (Wolters Kluwer, 2010)
CD10 is a cell surface peptidase expressed in a wide variety of normal and neoplastic tissues, including breast myoepithelial cells. In salivary glands, expression of CD10 has only been used to identify neoplastic myoepithelial cells of pleomorphic adenomas and myoepithelial carcinomas. However, its accuracy in other salivary tumors with myoepithelial component has yet to be analyzed. We examined 72 salivary tumors with myoepithelial differentiation using immunohistochemical technique to detect CD10. In salivary glands, CD10 expression was not detected in myoepithelial cells. Only fibrocytes within the intralobular stroma were CD10 positive. In neoplastic myoepithelial cells, CD10 expression was found in 25.71% of benign and 32.43% of malignant neoplasms. When the different groups of tumors were compared, epithelial-myoepithelial carcinomas (EMEC) showed a stark contrast with the others (83.3% of cases with CD10 expression). Surprisingly, adenoid cystic carcinomas and basal cell adenomas were negative in 100% of the cases. Myoepitheliomas, pleomorphic adenomas, and myoepithelial carcinomas were positive in 27.7%, 30.0%, and 40% of the cases, respectively. In conclusion, salivary neoplastic myoepithelial cells gain CD10 expression in relation to their normal counterparts. However, the gain of this protein is not a sensitive marker for detecting myoepithelial cells in the majority of the tumors, except for EMEC. The high expression of CD10 by this carcinoma can be a valuable tool to separate EMEC from the tubular variant of adenoid cystic carcinomas in small incisional biopsies, where the precise diagnosis may be impossible.